2020
DOI: 10.1101/2020.12.04.412379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biogenesis of RNA-containing extracellular vesicles at endoplasmic reticulum membrane contact sites

Abstract: SummaryRNA transferred via extracellular vesicles (EVs) can influence cell and tissue phenotypes; however, the biogenesis of RNA-containing EVs is poorly understood and even controversial. Here, we identify the conserved endoplasmic reticulum membrane contact site (MCS) linker protein VAP-A as a major regulator of the RNA and RNA-binding protein content of small and large EVs. We also identify a unique subpopulation of secreted small EVs that is highly enriched in RNA and regulated by VAP-A. Functional experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 88 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…KRAS (Cha et al, 2015), HuR (Mukherjee et al, 2016), MEX3C (Lu et al, 2017), Ago2 (Gibbings et al, 2009;Mckenzie et al, 2016), and IGF2BP1 (Ghoshal et al, 2019) have all been shown to have some effect on EV miRNA loading (Figure 2c). In an unbiased assessment of RBPs, Statello et al carried out EMSA of EV protein incubated with either total EV RNA, cellular mRNA or cellular miRNA, identifying 90 interacting proteins; one (MVP) was functionally validated, while five others (HNRNPA2B1, HNRNPK, HNRNPU, NSUN2 and VAP-A) were demonstrated to have involvement in independent studies (Barman et al, 2020;Kossinova et al, 2017;Villarroya-Beltri et al, 2013;Zietzer et al, 2020). On the other hand, in 2019 it was reported that many of these RBPs, including hnRNPA2B1 and MVP, were not associated with EVs, but were co-isolated contaminants, highlighting the importance of defined EV populations (Jeppesen et al, 2019).…”
Section:  Ev Rna Association With Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…KRAS (Cha et al, 2015), HuR (Mukherjee et al, 2016), MEX3C (Lu et al, 2017), Ago2 (Gibbings et al, 2009;Mckenzie et al, 2016), and IGF2BP1 (Ghoshal et al, 2019) have all been shown to have some effect on EV miRNA loading (Figure 2c). In an unbiased assessment of RBPs, Statello et al carried out EMSA of EV protein incubated with either total EV RNA, cellular mRNA or cellular miRNA, identifying 90 interacting proteins; one (MVP) was functionally validated, while five others (HNRNPA2B1, HNRNPK, HNRNPU, NSUN2 and VAP-A) were demonstrated to have involvement in independent studies (Barman et al, 2020;Kossinova et al, 2017;Villarroya-Beltri et al, 2013;Zietzer et al, 2020). On the other hand, in 2019 it was reported that many of these RBPs, including hnRNPA2B1 and MVP, were not associated with EVs, but were co-isolated contaminants, highlighting the importance of defined EV populations (Jeppesen et al, 2019).…”
Section:  Ev Rna Association With Proteinsmentioning
confidence: 99%
“…Many of the RBPs that have been identified as involved in RNA packaging (HNRNPA2B1, HNRNPA1, YBX-1, SYNCRIP and HNRNPU) were found to interact directly with the tetraspanin CD81, or two of its interacting proteins, ICAM-1 and EWl-2 (Perez-Hernandez et al, 2013). Cellular RNA distribution is also highly assymetric (Benoit Bouvrette et al, 2018;Khong et al, 2017;Matheny et al, 2019), and recent studies have indicated the possiblity that RNA loading of EVs is linked to organellar structures such as the nucleus (Lässer et al, 2017) and endoplasmic reticulum (Barman et al, 2020). also identified a striking 81% overlap between the protein interactome of the autophagy component phospholipid-conjugated LC3 and the EV proteome, with a heavy enrichment for RBPs.…”
Section:  Ev Rna Association With Proteinsmentioning
confidence: 99%
“…A key question in the EV field is how both protein and RNA cargo is distributed across the population. Barman et al demonstrated that within "small EVs" only 10% of the total EVs (the denser fraction) contained 90% of the RNA content [106]. Importantly, observations of this kind suggest the intriguing possibility that different biogenesis pathways are used to generate specific and functionally varied types of EVs.…”
Section: Ev Function and Cargomentioning
confidence: 99%
“…In this context consideration of the heterogeneity of EVs is of critical importance. Recently, it was found that a light subpopulation of small EVs contained around nine-fold less RNA per EV than a dense subpopulation (Barman et al, 2020). Thus, EV sub-types may derive from different intracellular locations that contain different RNA-protein complexes/RNA granule types.…”
Section: Molecular Motorsmentioning
confidence: 99%